Inhibition of SC4MOL and HSD17B7 shifts cellular sterol composition and promotes oligodendrocyte formation. Issue 1 (21st October 2021) - Pleshinger, Matthew J; Friedrich, Ryan M.; Hubler, Zita; Rivera-León, Adrianna M.; Gao, Farrah; Yan, David; Sax, Joel L.; Srinivasan, Ramya; Bederman, Ilya; Shick, H. Elizabeth; Tesar, Paul J.; Adams, Drew J.
Abstract : Inhibition of two additional cholesterol biosynthesis enzymes, SC4MOL and HSD17B7, and accumulation of their 8, 9-unsaturated sterols enhance formation of oligodendrocytes. We have also identified novel inhibitors of SC4MOL and HSD17B7. Abstract : While the cholesterol biosynthesis pathway has been extensively studied, recent work has forged new links between inhibition of specific sterol pathway enzymes, accumulation of their unique sterol substrates, and biological areas as diverse as cancer, immunology, and neurodegenerative disease. We recently reported that dozens of small molecules enhance formation of oligodendrocytes, a glial cell type lost in multiple sclerosis, by inhibiting CYP51, Sterol 14-reductase, or EBP and inducing cellular accumulation of their 8, 9-unsaturated sterol substrates. Several adjacent pathway enzymes also have 8, 9-unsaturated sterol substrates but have not yet been evaluated as potential targets for oligodendrocyte formation or in many other biological contexts, in part due to a lack of available small-molecule probes. Here, we show that genetic suppression of SC4MOL or HSD17B7 increases the formation of oligodendrocytes. Additionally, we have identified and optimized multiple potent new series of SC4MOL and HSD17B7 inhibitors and shown that these small molecules enhance oligodendrocyte formation. SC4MOL inhibitor CW4142 induced accumulation of SC4MOL's sterol substrates in mouse brain and represents an in vivo probe of SC4MOL activity. Mechanistically, the cellular accumulation of these 8, 9-unsaturated sterols represents a central driver of enhanced oligodendrocyte formation, as exogenous addition of purified SC4MOL and HSD17B7 substrates but not their 8, 9-saturated analogs promotes OPC differentiation. Our work validates SC4MOL and HSD17B7 as novel targets for promoting oligodendrocyte formation, underlines a broad role for 8, 9-unsaturated sterols as enhancers of oligodendrocyte formation, and establishes the first high-quality small molecules targeting SC4MOL and HSD17B7 as novel tools for probing diverse areas of biology.